Sustainable building cladding: balancing embodied carbon and protection against blast driven fragmentation penetration - Laycock, Angela; Helliker, Aimee; Critchley, Richard; Hazael, Rachael (Sage, 2026)
External building cladding provides not only protection from environmental factors, but it can also provide a barrier from extreme events such as explosions. The majority of buildings do not have protective design specifications, but may still be threatened by a terrorist attack or accidental explosion. This study investigates the performance of construction materials exposed to fragment impact, representing a hazard from Improvised Explosive Devices (IEDs). A variety of external cladding materials with different material properties and levels of embodied carbon were subject to steel sphere impacts driven by a gas gun. The V50 ballistic limit was calculated for each material which enabled the production of a novel material selection chart of Global Warming Potential versus V50 ballistic limit. Results showed that protection levels are independent of embodied carbon content, and that thickness and areal density have a weak positive correlation with V50. Some refinement can be achieved by grouping materials according to their morphology, this also had an effect on the dynamic impact failure mechanisms which are explored. Perforation limits are determined for each material, showing significant variations between material types and differences related to the size of the ball bearing impactor. These factors limit the applicability of deep penetration models. The effect of ball bearing size is analysed concluding that an 8 mm sphere is a repeatable and representative fragment threat. The results show that protection levels varied considerably across the materials tested and all were below the velocity expected from blast driven ball bearings. This highlights the importance of understanding protection levels to ensure that people are not injured through walls that they thought would protect them from external threats.
Keywords: 4005 Civil engineering; 4016 Materials engineering; 4017 Mechanical engineering; low carbon; building protection; material selection; impact; improvised explosive devices